2012
DOI: 10.1007/s10546-011-9692-3
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating the Absorption Contribution on $${C_{n^{2}}}$$ Estimates with a Large-Aperture Scintillometer

Abstract: Large-aperture scintillometers (LAS) are often used to characterize atmospheric turbulence by measuring the structure parameter of the refractive index C n 2 . However, absorption phenomena can lead to an overestimation of C n 2 . By applying an accurate numerical filtering technique called the Gabor transform to the signal output of a LAS, we improved our knowledge of the accuracy of the measured C n 2 by determining and attenuating the contribution of absorption. Two studies are presented on a 12-day dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similarly, C 2 M can be obtained from the imaginary part of the AERISP (C 2 n, Im ). Although the LAS was widely used to measure the sensible heat flux along the propagation path, only the high-frequency part of the light intensity fluctuation could be provided, and the low-frequency light intensity was often discarded (Solignac et al, 2012). Thus, a specially designed LAS (see details in Sect.…”
Section: R M Yuan Et Al: a New Methods For Estimating Aerosol Mass mentioning
confidence: 99%
“…Similarly, C 2 M can be obtained from the imaginary part of the AERISP (C 2 n, Im ). Although the LAS was widely used to measure the sensible heat flux along the propagation path, only the high-frequency part of the light intensity fluctuation could be provided, and the low-frequency light intensity was often discarded (Solignac et al, 2012). Thus, a specially designed LAS (see details in Sect.…”
Section: R M Yuan Et Al: a New Methods For Estimating Aerosol Mass mentioning
confidence: 99%
“…Therefore, the light intensity variances induced by the real and imaginary parts can be detected separately at high frequencies and low frequencies from the sLAS measurements. The real part of AERISP be detected, and the low-frequency light intensity is often discarded (Solignac et al, 2012). Thus, a specially designed sLAS ( sea details in Section 3) is needed (Yuan et al, 2015).…”
Section: Measurement Methods 15mentioning
confidence: 99%
“…Besides these applications, knowledge of the crosswind may be important for the quality of scintillometer data itself. Use of a dynamic bandpass filter has been suggested to account for the shift in frequency spectrum with crosswind (Solignac et al, 2012;Van Kesteren et al, 2015), as an inappropriate bandpass can artificially reduce Cn 2 . Whether related to the footprint, atmospheric conditions or basic principles of scintillometer measurement, it has been suggested that low and/or high crosswind speed has an impact on the accuracy of structure parameters and fluxes, particularly for two-wavelength systems (Evans, 2009;Ward et al, 2015b).…”
Section: Variable Wind Fieldmentioning
confidence: 99%